2012
DOI: 10.1186/1471-2458-12-7
|View full text |Cite
|
Sign up to set email alerts
|

Active living neighborhoods: is neighborhood walkability a key element for Belgian adolescents?

Abstract: BackgroundIn adult research, neighborhood walkability has been acknowledged as an important construct among the built environmental correlates of physical activity. Research into this association has only recently been extended to adolescents and the current empirical evidence is not consistent. This study investigated whether neighborhood walkability and neighborhood socioeconomic status (SES) are associated with physical activity among Belgian adolescents and whether the association between neighborhood walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 58 publications
6
72
1
Order By: Relevance
“…The proportion of active and passive commuting by education towards the outskirts). This is consistent with the findings and results gathered in other studies (Christiansen, Madsen, Schipperijn, ErsbĂžll, & Troelsen, 2014;De Meester et al, 2012;Frank et al, 2010;Freeman et al, 2013). Adams et al (2014) concluded that areas with high walkability are characterized by an accumulation of a large number of inhabitants and higher commuting accessibility (e.g., Hong Kong or Bogota in Colombia).…”
Section: Discussionsupporting
confidence: 91%
“…The proportion of active and passive commuting by education towards the outskirts). This is consistent with the findings and results gathered in other studies (Christiansen, Madsen, Schipperijn, ErsbĂžll, & Troelsen, 2014;De Meester et al, 2012;Frank et al, 2010;Freeman et al, 2013). Adams et al (2014) concluded that areas with high walkability are characterized by an accumulation of a large number of inhabitants and higher commuting accessibility (e.g., Hong Kong or Bogota in Colombia).…”
Section: Discussionsupporting
confidence: 91%
“…For example, the association between children's biking and street connectivity was found to be positive in one study (Trapp et al 2011) but negative in another (Van Dyck et al 2009). Other studies found no associations between environmental measures and children's biking (e.g., Ducheyne et al 2013;de Meester et al 2012;de Vries et al 2010).…”
Section: 3mentioning
confidence: 91%
“…The retail floor area ratio is then added to achieve a more favorable result [12]. This four-component walkability index is used in many studies concerning walkability [55][56][57][58][59][60][61]. However, the application of the four-component walkability index is still limited.…”
Section: Introductionmentioning
confidence: 99%